IMMU-03. SUPPRESSION OF ONCOMETABOLITE 2-HYDROXYGLUTRATE PRODUCED BY MUTANT IDH1 GLIOMA WITH AGI-5198 ENHANCES THE EFFICACY OF RADIOTHERAPY AND IMMUNE CHECKPOINT BLOCKADE ELICITING IMMUNOLOGICAL MEMORY - Kadiyala, Padma (Neuro Oncol, 2019)
Patients with mutant IDH1 gliomas survive ~3.8 year longer than patients harboring wildtype IDH1 glioma, irrespective of histology or genetic lesions, making mutant IDH1 an essential prognostic indicator. Mutant IDH1 gliomas are highly infiltrative with a high incidence of relapse. We are studying a low grade glioma subtype, genetically characterized by inactivating mutations in α-thalassemia/mental retardation syndrome X-linked (ATRX) gene, TP53 and gain of function mutations in isocitrate dehyrdogenase 1 (mIDH1). Mutation in IDH1 converts α-ketoglutrate (αKG) to 2-hydroxyglutarate (2HG), an oncometabolite that inhibits histone and DNA demethylases, leading to a hypermethylated tumor phenotype [1]. This leads to epigenetic reprograming of the tumor transcriptome. The role of 2HG as an immune regulator in the mIDH1 glioma tumor microenvironment remains to be elucidated. Herein, we investigate whether 2HG produced by mIDH1 glioma in the tumor microenvironment mediating antitumor immunity. We used mIDH1 inhibitor AGI-5198 to abrogate the neomorphic enzymatic activity of IDH1R132H in a transplantable mIDH1 glioma mouse model. Animals were implanted with mIDH1 tumor neurospheres and they were systemically administered with AGI-5198. Our results indicate that pharmacological inhibition of IDH1R132H enzymatic function significantly prolongs the median survival (MS) of mIDH1 glioma bearing mice (~1.5-fold vs controls); eliciting strong antitumor activity, eradicating 40% of the established mIDH1 gliomas. Our results also demonstrate that antitumor immunity induced by 2HG inhibition is enhanced when combined with standard of care (temozolomide and radiation) and anti-PDL1 immune checkpoint blockade. In addition, when the long-term survivors (>90 days) were rechallenged with mIDH1 tumor cells in the contralateral hemisphere, without further treatment, all the mice remained tumor free, indicating the development of anti-glioma immunological memory. Collectively, these findings support the clinical testing of AGI-5198 as an adjuvant therapy and a novel immunotherapeutic strategy for treating patients with mIDH1 glioma.